Krüpple-like factors in cardiomyopathy: emerging player and therapeutic opportunities - Gui, Le-Kun; Liu, Huang-Jun; Jin, Li-Jun; Peng, Xiao-Chun (Frontiers in Cardiovascular Medicine, 2024)
Cardiomyopathy, a heterogeneous pathological condition characterized by changes in cardiac structure or function, represents a significant risk factor for the prevalence and mortality of cardiovascular disease (CVD). Research conducted over the years has led to the modification of definition and classification of cardiomyopathy. Herein, we reviewed seven of the most common types of cardiomyopathies, including Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC), diabetic cardiomyopathy, Dilated Cardiomyopathy (DCM), desmin-associated cardiomyopathy, Hypertrophic Cardiomyopathy (HCM), Ischemic Cardiomyopathy (ICM), and obesity cardiomyopathy, focusing on their definitions, epidemiology, and influencing factors. Cardiomyopathies manifest in various ways ranging from microscopic alterations in cardiomyocytes, to tissue hypoperfusion, cardiac failure, and arrhythmias caused by electrical conduction abnormalities. As pleiotropic Transcription Factors (TFs), the Krüppel-Like Factors (KLFs), a family of zinc finger proteins, are involved in regulating the setting and development of cardiomyopathies, and play critical roles in associated biological processes, including Oxidative Stress (OS), inflammatory reactions, myocardial hypertrophy and fibrosis, and cellular autophagy and apoptosis, particularly in diabetic cardiomyopathy. However, research into KLFs in cardiomyopathy is still in its early stages, and the pathophysiologic mechanisms of some KLF members in various types of cardiomyopathies remain unclear. This article reviews the roles and recent research advances in KLFs, specifically those targeting and regulating several cardiomyopathy-associated processes.